2017
DOI: 10.1177/1049731517732837
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Recovery-Oriented Cognitive–Behavior Approach for Chinese With Severe Mental Illness

Abstract: Purpose: Hope and meaning in life are essential components of personal growth and happiness. Built on the recovery model, this study attempted to evaluate the effects of a recovery-oriented cognitive–behavior approach (CBA) in enhancing hope and meaning in life among a group of people with severe mental illness in Hong Kong. Method: A matched-pair comparison approach was adopted. Twenty-seven experimental group participants received recovery-oriented CBA, while 25 participants received standard counseling serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Psychological resilience enables individuals to plan for achieving goals, develop a positive self-view, have confidence in their abilities, acquire skills in assertiveness, readiness to listen to others, respect for the feelings and beliefs of others, create order, stability, and security in their personal life, feel capable of facing problems, and confront challenges in a problem-solving manner; using these adaptive strategies may reduce negative emotions and consequently improve cognitive and emotional functioning(33).Additionally, psychological resilience involves training in the concept of change, familiarization with the process of confronting change, adopting a flexible outlook in dealing with life changes, learning to recognize and control emotions and feelings in crisis and difficult conditions, enabling individuals to have greater control over their unpleasant feelings at the time of a negative event occurrence, engage more effectively in planning for resolving the negative event, and instead of focusing on negative emotions and feelings caused by the situation, focus on the positive and bright aspects of the situation and their positive emotions(9,12,13).Another finding of this research showed that the recovery-oriented cognitive therapy intervention program was effective in improving the quality of life of schizophrenia patients. This finding is somewhat consistent with the prior results(8,24, 28,34). To explain this finding, it can be stated that increased connection, beginning to trust, developing more energy, and having greater access to motivation, all these factors in recovery-oriented cognitive therapy shift the focus towards a life that the person truly wants, such as having a home, a job, starting a family; recovery-oriented cognitive therapy uses the term "dreams" for these life goals; dreams are big, meaningful, and motivational(24).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Psychological resilience enables individuals to plan for achieving goals, develop a positive self-view, have confidence in their abilities, acquire skills in assertiveness, readiness to listen to others, respect for the feelings and beliefs of others, create order, stability, and security in their personal life, feel capable of facing problems, and confront challenges in a problem-solving manner; using these adaptive strategies may reduce negative emotions and consequently improve cognitive and emotional functioning(33).Additionally, psychological resilience involves training in the concept of change, familiarization with the process of confronting change, adopting a flexible outlook in dealing with life changes, learning to recognize and control emotions and feelings in crisis and difficult conditions, enabling individuals to have greater control over their unpleasant feelings at the time of a negative event occurrence, engage more effectively in planning for resolving the negative event, and instead of focusing on negative emotions and feelings caused by the situation, focus on the positive and bright aspects of the situation and their positive emotions(9,12,13).Another finding of this research showed that the recovery-oriented cognitive therapy intervention program was effective in improving the quality of life of schizophrenia patients. This finding is somewhat consistent with the prior results(8,24, 28,34). To explain this finding, it can be stated that increased connection, beginning to trust, developing more energy, and having greater access to motivation, all these factors in recovery-oriented cognitive therapy shift the focus towards a life that the person truly wants, such as having a home, a job, starting a family; recovery-oriented cognitive therapy uses the term "dreams" for these life goals; dreams are big, meaningful, and motivational(24).…”
supporting
confidence: 93%
“…The current study aimed to determine the effectiveness of and the person navigates their path towards a desirable life (8). This therapeutic approach strives to help the individual understand their ineffective cognitive and behavioral responses and create functional responses that lead to life satisfaction and better mental health (34). Moreover, recovery-oriented cognitive therapy is not a reflective process but an active one.…”
Section: Discussionmentioning
confidence: 99%
“…(51) In the same direction study carried by Wong D. et al (2019) who examine the impact of a recovery-oriented cognitive-behavior approach among a group of people with schizophrenia that showed improving in the mental health recovery process and a sense of hope for those people. (52) While contrast to the result of Goh Y. et al (2023) who examine the effectiveness of their recovery program in improving personal-recovery outcomes among people with psychiatric disorders, their result suggested that a modest improvement in personal-recovery scores among participants during the post-program periods and follow-ups compared to those in the non-recovery groups. (53) In another hand, the results of the present study denote that the patients who have a high level of recovery have a high level of self-management.…”
Section: Discussionmentioning
confidence: 81%
“…Therapists’ belief in treatment potential significantly impacts outcomes [ 33 ]. Over the past decade, literature has consistently emphasized recovery-oriented practices for improving patient outcomes, including enhanced functioning, goal setting, reduced legal issues, and decreased hospital admissions [ 34 35 ]. Consequently, mental health services increasingly integrate recovery paradigms into treatment strategies [ 36 ].…”
Section: Introductionmentioning
confidence: 99%